2019
DOI: 10.1093/eurheartj/ehz747.0118
|View full text |Cite
|
Sign up to set email alerts
|

459Direct oral anticoagulants are an effective therapy for left ventricular thrombus formation

Abstract: Background and aim Left ventricular thrombus is a frequent complication of myocardial infarction (MI) and heart failure with severely depressed ejection fraction. Once diagnosed, anticoagulation for up to 6-months is recommended, but clinical experience with direct oral anticoagulation (DOAC) is limited to a few case reports. Our aim is to test DOAC LV thrombus resolution efficacy against warfarin. Methods Single-centre retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…After systematic review, a total of 6 studies (2 fully published papers and 3 published abstracts), in addition to our current study were included (n ¼ 408 for DOACs; n ¼ 1207 for VKA). [30][31][32][33][34] Overall, there was no significant differences between patients treated with DOACs versus VKAs for LVT with respect to odds for unresolved thrombus (OR 0.61, 95% CI 0.26,1.41), embolic events (OR 1.24, 95% CI 0.90,1.69), or bleeding events (OR 1.13, 95% CI 0.74,1.72) ( Figure 2). No significant heterogeneity was noted.…”
Section: Meta-analysismentioning
confidence: 98%
“…After systematic review, a total of 6 studies (2 fully published papers and 3 published abstracts), in addition to our current study were included (n ¼ 408 for DOACs; n ¼ 1207 for VKA). [30][31][32][33][34] Overall, there was no significant differences between patients treated with DOACs versus VKAs for LVT with respect to odds for unresolved thrombus (OR 0.61, 95% CI 0.26,1.41), embolic events (OR 1.24, 95% CI 0.90,1.69), or bleeding events (OR 1.13, 95% CI 0.74,1.72) ( Figure 2). No significant heterogeneity was noted.…”
Section: Meta-analysismentioning
confidence: 98%
“…Seventeen studies reported on LV thrombus resolution. [7][8][9][10][17][18][19][20][21][23][24][25][26][27][28][29][30] Twelve studies reported no significant difference in LV thrombus resolution between DOACs and VKAs. [7][8][9][10]18,23,24,[26][27][28][29][30] Three studies 19,20,25 significantly greater LV thrombus resolution with DOACs over the entire study period, and 2 other studies 17,21 found initial resolution to be faster with DOACs, but no significant differences in resolution when measured over the entire study period.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…[7][8][9][10][17][18][19][20][21][23][24][25][26][27][28][29][30] Twelve studies reported no significant difference in LV thrombus resolution between DOACs and VKAs. [7][8][9][10]18,23,24,[26][27][28][29][30] Three studies 19,20,25 significantly greater LV thrombus resolution with DOACs over the entire study period, and 2 other studies 17,21 found initial resolution to be faster with DOACs, but no significant differences in resolution when measured over the entire study period. Jones et al reported consistently higher LV thrombus resolution with DOACs compared with VKAs at different time points through the 1-year follow-up period (82% vs 64.4%, P = 0.0018) even after adjusting for baseline variables (OR 1.8, 95% CI 1.2-2.9).…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 2 more Smart Citations